1978
DOI: 10.1007/bf02235293
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation Par Les Moutons D'herbages Sans Plantations, Au Ghana

Abstract: A study conducted into the utilisation by sheep of herbage under a mango/cashew plantation at Kade (Ghana) showed the native herb, Asystasia gangetica to be the most preferred herbage. Centrosema pubescens was preferred to Pueraria phaseoloides. The physical condition of the herbage affected their preference but the crude protein content did not have any influence. The mean daily digestible dry matter intake of yearling rams (g/kg W0.75) was 34, 31 and 39 for animals on Brachiaria lata/Pueraria phaseoloides, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Asiedu, Oppong and Opoku (1978) found that sheep gained 64 g/day on grass during the wet season, whilst earlier studies at this Institute showed that sheep gained 67 g/day on good quality Digitaria smutsii and 26 g/day on low quality Cynodon plectostachus pasture. Climatic conditions, heavy rains during the night and internal parasites were probably responsible for these rather low gains.…”
Section: Concentrates For Sheep On Pasturementioning
confidence: 75%
“…Asiedu, Oppong and Opoku (1978) found that sheep gained 64 g/day on grass during the wet season, whilst earlier studies at this Institute showed that sheep gained 67 g/day on good quality Digitaria smutsii and 26 g/day on low quality Cynodon plectostachus pasture. Climatic conditions, heavy rains during the night and internal parasites were probably responsible for these rather low gains.…”
Section: Concentrates For Sheep On Pasturementioning
confidence: 75%
“…It has many positive qualities that bene t humans but have escaped human attention. The upright nature of this plant, its ability to thrive in shade, its aroma and palatability, and its thornless physical characteristics all contribute to its attractiveness to grazing animals, and it is therefore used as forage for cattle, goats, and sheep in Africa and Southeast Asia (Adetula 2004;Asiedu et al 1978). The crude protein content of this plant, which is similar to that of cassava leaves, is signi cantly higher than that of common grasses, while its mineral content indicates that Asystasia is a good source of Ca, P, Mn, Zn, and Cu for cattle (Khalil 2016).…”
Section: Discussionmentioning
confidence: 99%
“…With this in mind and also the fact that para grass is firmly established along waterways on the Research Station it was decided to test it under the tree crops. Earlier studies (Asiedu et al 1978) had shown that swards of predominantly centro and puero adapted well to 6-week grazing intervals. International Livestock Centre for Africa (1979) also suggests defoliation intervals of 6 weeks for humid African grasses.…”
Section: Introductionmentioning
confidence: 93%